Analysis of Jekdes Online Transportation Application System in Increasing Sales Profit of Jekdes Business Partners in Region 6 Sukabumi Regency - Asep Saepul Gaos; Elan Eriswanto; Andri Indrawan (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
Technological developments are increasingly giving changes in the business world, especially in small-scale businesses. The presence of transportation Online in the form of an application that is a feature mobile phone called Jekdes, provides extraordinary assistance in making it easier for small traders to do business well and earn good profits. This study aims to analyze the transportation application system online Jekdesused by Jekdes business partners in increasing sales profit. The method used is qualitative research with descriptive and associative approaches. The results of the study show that there are weaknesses in the system used by Jekdes which is connected to partners so that business partners are not satisfied with the service from the application, the profit received is only slightly from sales through the Jekdes application, thus data analysis shows the profit received by the business partner of the village more manual systems than the results of the applications used.